Trajectories to high income: Growth dynamics in Japan, the People's Republic of China, and the Republic of Korea - Michael Murach; Helmut Wagner; Jungsuk Kim; Donghyun Park (Asian Development Bank (ADB), 2020)
We analyze and compare the patterns of economic growth and development in the Japan, the People's Republic of China, and the Republic of Korea in the postwar period. The geographical proximity and cultural affinity between the three countries, as well as the key role of the development state in the economies, suggest that an analytical comparison would be a meaningful and valuable exercise. Furthermore, Japan and the Republic of Korea are two of the few economies that have jumped from middle income to high income in a short period and thus offer potentially valuable lessons for the PRC. We use Cobb-Douglas production functions to assess the long-run equilibrium relationships between per capita gross domestic product, capital, and labor by means of cointegrated vector autoregressive models. We show that such equilibrium relationships cannot be rejected for all three countries, while the evidence is stronger for the PRC and the Republic of Korea than for Japan. Our hypothesis tests show that the estimated Cobb-Douglas production functions display coefficients of capital and employment that sum up to 1 and broken linear trends that can be attributed to structural breaks and (changes in) total factor productivity growth. We observe a striking similarity between the experience in the Republic of Korea and the PRC, which gives some optimism that the PRC may be capable of graduating to high income, like the Republic of Korea.
Keywords: E23; O47; O53; O57; P52; 330; aggregate production function; comparative economic growth; economic development; Japan; People's Republic of China; Republic of Korea